2021
DOI: 10.1088/1757-899x/1166/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antibacterial and antioxidant activities of lemongrass (Cymbopogon citratus) essential oil and its fractions obtained by vacuum distillation

Abstract: Lemongrass (Cymbopogon citratus) essential oil (raw oil) is a natural product with many biological activities and is commonly used in the food and cosmetic industries. In this study, fractions of lemongrass essential oil were segregated from raw oil by vacuum fractionation. These fractions were then examined for their constitution, antioxidant and antimicrobial activities. Gas chromatography-mass spectrometry results indicated a difference in constitution and content of compounds among the fractions and raw oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that the major constituents of EO are α-citral, β-citral, geraniol, nerol, terpinolene, geranyl acetate, citronellal, myrcene, and terpinol methylheptenone [37]. In one study, α-citral (44.97%), α-citral (33.06%), and myrcene (7.68%) were identified as the major compounds of lemongrass EO [61]. The effects of different treatments on the weight loss (%) of strawberry fruits during the 16 days of storage period in both experiments are shown in Figure 2.…”
Section: Chemical Constituents Of Lemongrass Oilmentioning
confidence: 98%
“…Previous studies have reported that the major constituents of EO are α-citral, β-citral, geraniol, nerol, terpinolene, geranyl acetate, citronellal, myrcene, and terpinol methylheptenone [37]. In one study, α-citral (44.97%), α-citral (33.06%), and myrcene (7.68%) were identified as the major compounds of lemongrass EO [61]. The effects of different treatments on the weight loss (%) of strawberry fruits during the 16 days of storage period in both experiments are shown in Figure 2.…”
Section: Chemical Constituents Of Lemongrass Oilmentioning
confidence: 98%